Psychological Interventions to Achieve Post-Traumatic Growth (PTG) after the Covid-19 Pandemic: a Systematic Literature Study - Adawia M, Rabiatul; Hayati, Elli Nur; Urbayatun, Siti (Journal of Educational, Health and Community Psychology, 2023)
This article examines effective psychological interventions to enhance Post traumatic growth (PTG) during the COVID-19 pandemic. Pandemic situation, causing extensive impacts, affects various aspects, including mental health. If not addressed properly, it can result in prolonged consequences such as heightened stress, increased anxiety, depression, and Post Traumatic Stress Disorder (PTSD). This research employs a systematic literature review method based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Article analysis criteria were formulated using the Populations, Interventions, Comparison, Outcomes, and Time (PICOT) framework. Total of 254 articles were collected from various databases, and after the screening process, eight articles that met the analysis criteria remained. The analysis reveals that several effective interventions for enhancing Post traumatic growth in the context of the Covid-19 pandemic include Mindfulness-Based Cognitive Therapy (MBCT), photography intervention, expressive writing, Character Strength-Based Intervention, group counseling, Psychological Intervention (Professionals in emotional crisis: COVID-19), Online Self-Distancing Intervention: to promote emotional regulation and post traumatic growth, Compassion & Growth Workshop, and psychological consultations. Keywords: Covid-19, interventions, post-traumatic growth